Rumination and drug craving scores in Chinese male patients with methamphetamine and heroin use disorders: a cross-sectional study - Yinxue Mao; Deyang Li; Dongmei Wang; Yang Tian; Jiajing Chen; Lianglun Jia; Xiaotao Wang; Xiang-Yang‍ Zhang‍‍ (Substance Abuse Treatment, Prevention, and Policy)
Abstract Background Rumination is an essential trans-diagnostic process associated with substance use disorders (SUDs) in psychopathology. In China, methamphetamine and heroin have become major illegal drugs, but the role of rumination in their use remains unclear. The objective of this study was to investigate the relationship between rumination subtypes and drug craving in patients with methamphetamine use disorder (MAUD) and 81 patients with heroin use disorder (HUD). Methods A total of 489 participants, including 408 patients with MAUD and 81 patients with HUD, were recruited from a rehabilitation center. Participants were screened for inclusion criteria, and the Obsessive Compulsive Drug Use Scale (OCDUS) was used to assess drug craving. Rumination was assessed using the Ruminative Responses Scale (RRS), categorized into three dimensions: symptom rumination, brooding, and reflective pondering. Correlational and multiple regression analyses were conducted to examine associations between rumination and craving. Results Compared to patients with MAUD, patients with HUD had significantly higher RRS and OCDUS total score (42.51 vs 39.71 and 25.99 vs 20.95, both p < 0.01). In patients with MAUD, the OCDUS total score was positively correlated with the total score (r = 0.298, p < 0.01) and all subscale scores of the RRS (for reflective pondering, r = 0.180; for brooding, r = 0.230; for symptom rumination, r = 0.325; all p < 0.01). However, in patients with HUD, only symptom rumination was positively associated with the OCDUS total score (r = 0.247, p < 0.05). Multiple regression showed symptom rumination was independently associated with OCDUS total score in both groups (for patients with MAUD, β = 0.324, p < 0.001; for patients with HUD, β = 0.252, p < 0.05). Conclusions Our findings suggest that rumination shows different effects on craving in male patients with MAUD and HUD. Moreover, symptom rumination may have a significant influence on the connection between rumination and craving in individuals with MAUD and HUD.